SCIENTIFIC COLLABORATION IN PERSPECTIVE OF SELF-ORGANIZED SYSTEMS: a meta-theoretical study - Hilario, Carla Mara [UNESP]; Tognoli, Natalia Bolfarini [UNESP]; Cabrini Gracio, Maria Claudia [UNESP] (Univ Federal Campina Grande, 2016)
Analyzes the dynamics of scientific production process from the perspective of philosophy, with the contribution of the sociology of science. Aims to conduct a meta-theoretical study of Scientific Collaboration, from the Dynamic Systems Theory and the Self-organization Theory. This paper also use the methodology about meta-theoretical analysis Mu by Ritzer and describes the science and scientific collaboration as from selected theories. Identifies the work in the intellectual-internal, social-domestic and foreign intellectual axes and points out that each area has different characteristics according to its domestic laws, consolidated from its historical development and social context. Considers that the groups of researchers form spontaneously and this researchers organize themselves to choose their colaborators. It also considers that science can be treated as an autonomous and self-organizing system that is built from their own results, and with the interaction with the social context in which it operates.
Keywords: Scientific collaboration; Self-organizing systems; Self-organization of science